The Politeness of Speech Acts in Teaching and Learning Interactions Between Teachers and Students of SD Negeri 4 Sutopati Magelang - Nurhana Lisna Linawati; Harun Joko Prayitno (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This research aims to identify speech acts at SD Negeri 4 Sutopati school. The research data is the speech of teachers and students at SD Negeri 4 Sutopatiin school learning. The data collection techniques were free listening technique, recording technique, and note-taking technique. The data were obtained directly during classroom learning, as well as recordings of learning dialogues. The data analysis used intralingual and pragmatic methods. In this study, the validity of the data was tested by using the triangulation technique of data sources of students’ and teachers’ speech during learning and teaching which was then analysed based on the psychopragmatic approach. The speech acts found during teaching and learning are directive, representative, and there is politeness consisting of maxims of wisdom, maxims of generosity in the speech. The results of the research of directive speech acts are 9.56%, then representative 19.42%. While the maxim of wisdom is spoken as much as 3.1%, the maxim of generosity as much as 3.5%, which is done by teachers or students during learning. The utterances delivered are often spoken or spoken by students to teachers or teachers to students during learning and teaching, thus causing a speech act delivered in daily activities. Speech acts in SD Negeri 4 Sutopati can be used as Indonesian language learning materials at school.